Accuracy Assessment of the Eulerian Two-phase Model for the CFD Simulation of Gas Bubbles Dynamics in Alkaline Electrolyzers. Issue 1 (1st December 2022) - Dreoni, M; Balduzzi, F; Ferrara, G; Bianchini, A
Abstract: To date, the most industrially developed technology to produce green hydrogen is represented by alkaline water electrolysis (AWE). To improve on design and efficiency of these devices, however, multiphysics simulations based on Computational Fluid Dynamics (CFD) are needed, able to account for electrophysical phenomena and multiphase flows. Focusing on internal flow optimization, the requirements for CFD simulations are anyhow extremely challenging, since solving the gas bubbles' motion implies the solution of a two-phase flow characterized by very low Reynolds numbers and a high fraction of dispersed gas. Despite some interesting studies have been presented in the literature so far, validation of CFD results with detailed experimental measurements is quite rare and, therefore, the reliability of the adopted modelling approaches is not assessed yet. This study presents the results of a multivariate CFD analysis of an electrochemical cell and its validation through a literature test case. Bubbles generation is introduced as a source term, thus overlooking for the moment the electrochemistry to focus on fluid-dynamics. In particular, attention is given to the Eulerian multiphase modelling, investigating the influence of both the inter-phase interaction sub-models' settings (e.g., lift and drag forces, virtual-mass force) and the general settings of the simulation. The mean velocity field of the PIV-measured bubbles is considered to assess the accuracy of numerical predictions, while the available high-definition flow pictures allow a qualitative assessment of the bubbles size and location. CFD results are shown to be in decent agreement with experimental data and able to reproduce the key flow features such as the spreading of the bubble curtains and the gas shifting towards the inner part of the cell. The effect of the bubbles' diameter and of source layer thickness is also discussed.